IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON IMPROVING SMALL AND MEDIUM ENTERPRISES PERFORMANCE IN AN URBAN KAMPUNG: Case Study of Kampoeng Cyber RT 36 Neighbourhood of Patehan, Yogyakarta - , PAHALA HAMONANGAN LUMBAN GAOL, Jan Fransen, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
ICT has become an interesting phenomenon, specifically in the business world. It has contributed significant changes in many parts of the world where new SMEs emerged and challenged the domination of established corporations. However, although many SMEs have been able to seize its benefit, others are not so successful. Therefore, it draws curiosity as to how exactly ICT can give impact on the performance of the SMEs. This is the main concern of this research. To engage with it, the research came up with a question: How can SMEs utilize ICT to improve their business performance? The research pursued the answer to the question by devising a descriptive-case study, utilizing in-depth interviews, secondary data collection and field observation. The interviews were conducted with eleven respondents, consisting ten SME owners and the neighbourhood leader, in a neighbourhood in Yogyakarta City, called RT 36 of Patehan. The research found out that the residents of RT 36 are able to build a computer-internet network providing a 24-hour-a-day internet connection which they call âKampoeng Cyberâ network. It enables the SMEs in the kampung to integrate ICT into their business. As the result, most of them are able to increase their business performance. However, there are also some discrepancies in which the respondents with more extensive ICT intervention have less performance improvement than other respondents with less extensive ICT. It implies that having ICT interventions doesnât automatically improve the SMEsâ performance. Further enquiries showed that the performance improvement relates to the Absorptive Capacity of the SMEs. Absorptive Capacity has four dimensions, namely Acquisition, Assimilation, Transformation and Exploitation. Of the four dimensions, significant distinction among the respondents can be spotted in terms of Transformation. The SMEs that manage to significantly improve their performance are able to combine the new innovation with their old knowledge, put ICT into the context of their existing work system and properly merge the new innovation into their work mechanism. The research also found out that Absorptive Capacity has a strong relationship with entrepreneurship, social capital and networking of the SMEs. These aspects help the SMEs to break the barriers toward ICT absorption. The research finally concluded that SMEs can properly utilize ICT to improve their business performance by having adequate and proportional dimensions of Absorptive Capacity. Although all dimensions should be present, Transformation holds a significant role since it relates to placing ICT into the specific context of the SME. SMEs should also possess entrepreneurial capital, adequate networking and appropriate purpose of ICT intervention. Mere investment on ICT without full understanding of its own condition may make it difficult for an SME to integrate ICT into its work system and hamper its optimum utilization for performance improvement.